How oral infections can influence chronic kidney disease – a review of the literature - Pontes, Carla Cruvinel; Chikte, Usuf ME (African Journal of Nephrology, 2020)
A healthy mouth is necessary for optimal health and quality of life. However, oral health is often compromised in adults with chronic kidney disease (CKD). The aim of this review was to present the scientific foundations behind the connection between oral diseases and chronic kidney disease (CKD) in adults, discuss common oral conditions and their systemic effects, investigate biological pathways through which oral infections affect the body and provide guidelines for physicians/nephrologists. Prevalence of oral disease is increased in CKD, including periodontal disease, oral mucosal lesions, edentulousness, xerostomia, gingival overgrowth in immunosuppressed patients and potentially caries. There is moderate to strong evidence to support a negative impact of oral infections in CKD, particularly periodontal disease, with systemic inflammation, bacteraemia of oral origin, endothelial function and gut dysbiosis being potential pathways for this interaction. Poor oral health can be a hidden source of infection and has been associated with increased mortality in CKD patients. Elimination of potential foci for oral infections is crucial before renal transplantation. Frequent dental monitoring is crucial for these patients and should be part of a multidisciplinary approach to manage CKD, with special attention to end-stage kidney disease.